CHILDREN AND ROBOT: POSTHUMANISM READING ON RIKO THE SERIES - Susanto Susanto (Universitas Muhammadiyah Semarang, 2021)
The emergence of Indonesian young celebrities from Hijrah movement who made Islamic children's films as a means of da'wah (Islamic missionary) is interesting to be studied. Different from Nussa, Riko the Series is one of the children's Islamic films that raises the issue of religion, children and technology relations. This study aims to find the representation of robots and the relationship between robots and children in children Islamic film Riko the Series from the perspective of Post-humanism. This study is library study. The data is in forms of audio visual and verbal transcripts from Riko the Series film, official website and from interview with the initiators taken from internet. The data were collected and analyzed using documentation to explore the concepts of post-humanism and its relation to representation of robot and robot-young adult relation in Riko the Series film. Content analysis is used as method to analyze the relation between robot and children. The result of the study showed that Riko the Series represents post-humanism in the following aspects: 1) New awareness of religion toward technology which represented by the inclusion of robot Q110 to Modern Upper Middle class of Islamic family, 2) It places robot in relation to human being without undermine it as merely object by treat it as modern child caretaker who educate, protect and become the partner of children. However, the relation between robot and children are still unbalance in which robot is more dominant than children so that it creates over reliance and dependence on using robot to children.